Establishment of cryopreserved gene banks of European chestnut and cork oak (European Journal of Forest Research, 2010)
Cryopreservation of selected genotypes of European chestnut and cork oak was carried out in two laboratories in a project involving conservation of ﬁeld collections. Plant material was selected on the basis of disease resistance (chestnut), growth habit, phytosanitary performance and cork quality (cork oak). The cryopreservation technique comprised of vitriﬁcation of shoot apices isolated from in vitro stock shoot cultures (chestnut) and somatic embryos (cork oak). Forty-three out of 46 chestnut genotypes assayed survived the freezing process, but only 63% recovered their capacity to produce new shoots. After completion of multiplication and rooting steps, the surviving shoots produced plants that were morphologically identical to those derived from non-supercooled material. All 51 cork oak genotypes withstood freezing and were able to produce new somatic embryos through a process of secondary embryogenesis. Multiplication and germination of the recovered embryos enabled production of plants that were morphologically identical to those derived from nonsupercooled material. In light of the results obtained, longterm cryopreservation of these species is feasible, thereby ensuring conservation of valuable genotypes during ﬁeld evaluation